Synthesis of N-Acyl Pyrroles and Isoindoles from Oxime Ester Precursors via Transition-Metal-Catalyzed Iminocarboxylation - Su, Siyuan; Lee, Daesung (Synlett, 2022)
We describe Pt(II)- and Fe(III)-catalyzed iminocarboxylations of oxime esters conjugated with 1,3-enyne and an ortho-alkynylarene moiety, followed by a spontaneous O→N acyl migration of the enol carboxylate intermediate to generate N-acyl pyrroles and isoindoles. The reaction scope for pyrrole synthesis is general, whereas the formation of isoindoles has a relatively narrow scope because of their instability.
Keywords: iminocarboxylation; pyrroles; isoindoles; platinum catalysis; iron catalysis; oxime esters